Clinical Anatomy and Diagnostic Challenges in Peripheral Nerve Trauma for the Forensic Physician - Sorin Hostiuc; Oana-Mihaela Ciobanu; Eliza Popa; Raluca Căținaș; Amalia Maria Ionescu-Mihăiță; Andreea Sima; Ionut Negoi; Mihnea Costescu (Diagnostics, 2025)
Peripheral nerve injuries represent a significant challenge in legal medicine, and their proper management and evaluation are at the intersection of clinical medicine, anatomical science, and legal medicine. In this review, we aimed to integrate current knowledge about the anatomy, physiology, clinical management, and paraclinical assessment of peripheral nerve injuries, targeted explicitly for medical–legal practice. We conducted a comprehensive review of the medical–legal evaluation framework needed to evaluate peripheral nerve injuries, with particular emphasis on anatomical variations, imaging techniques, and methods to assess the timing of injury. Peripheral nerve injuries should be analyzed using a complex approach, which includes anatomical characteristics, variants, microanatomy, physiopathology, imaging, and other paraclinical evaluations. The analysis of causation and timing of injury should be heavily based on objective criteria and should be performed using a reproducible, objective, and scientifically based approach.